Spectral analysis of discrete fourier transform (DFT) using Matlab - Wong Shen Yuong (2023)
In this project, signal is analyzed by applying Discrete Fourier Transform (DFT), specifically Fast Fourier Transform (FFT) algorithm in MATLAB. In the spectral analysis, the parameters are identified for signal analysis and the effect of varying the DFT parameters is studied. This project is unique in such a way that students in the engineering courses find it difficult to master this subject, simply because they do not understand and visualize the complicated mathematical terms. Therefore, by applying the MATLAB software, the product of this project after documentation can be used for students to learn and experience the relevant theory in the electrical engineering courses.